BIOCHEMICAL CHANGES IN THE OVARY OF Liza abu DUE TO INFECTION WITH M yxobolm pfeifferi (Chidosporidia: Myxosporida) FROM BASRAH, IRAQ2- Moisture, Total Protein, Fat and Glycogen - Khalidah s. Al-Niaeem (Basrah Journal of Veterinary Research)
The changes in the biochemical composition of the ovary of Liza abu infected with Myxobolus pfeifferi were studied. The changes in the ovary are marked by a signiﬁcant increase in moisture and total protein content concurrent with a signiﬁcant decrease in fat and glycogen. . i In general, the changes in the biochemical composition occurred by the infection are " A same to those occurring during starvation of ﬁshes.